Coronary artery disease in adults with tetralogy of Fallot. (13th May 2019) - Egbe, Alexander C.; Ananthaneni, Sindhura; Jadav, Raja; Kothapalli, Srikanth; Rihal, Charanjit S.; Masood, Muhammad; Angirekula, Mounika; Najam, Maria; Bajwa, Numra; Tarek, Karim; Matthew, Jessey; Connolly, Heidi M.
Abstract: Background: There are limited data about outcomes of coronary artery disease (CAD) in adults with repaired tetralogy of Fallot (TOF). The purpose of this study was to describe the prevalence and treatment of CAD in adults with TOF, and the impact of CAD on long‐term survival. Methods: Retrospective review of MACHD database for adults with repaired TOF who underwent aortic root/selective coronary angiogram, 1990‐2017. Patients were categorized into three groups: (1) No CAD defined as normal coronary angiogram; (2) Mild CAD defined as ≤50% stenosis in all vessels; and, (3) Significant CAD defined as >50% stenosis in any vessel. Results: We identified 105 (23%) of 465 TOF patients that had angiograms; mean age 47 ± 12 years. The prevalence of mild CAD and significant CAD was 19% (20 patients) and 15% (16 patients), respectively. Of these 16 patient with significant CAD, 9 (56%), 3 (19%), and 4 (24%) patients received guideline directed medical therapy, percutaneous coronary intervention, and coronary artery bypass grafting, respectively. Significant CAD was an independent risk factor for mortality (HR: 2.03, 95% CI 1.64‐4.22, P  = .022) after adjustment for differences in age, and prevalence of atrial fibrillation and renal dysfunction. Conclusions: Based on a review of a selected cohort of 105 TOF patients, the prevalence of mild CAD and significant CAD was 19% and 15%, respectively. Significant CAD was an independent risk factor for mortality. There is need for more research to determine optimal noninvasive diagnostic strategies and optimal patient selections and methods for revascularization.